Studi Rencana Penentuan Titik Pemberhentian Angkutan Umum Massal Berbasis Jalan di Kabupaten Bogor pada Koridor 5 - Qoimah, Nur; Rulhendri, Rulhendri; Murtedjo, Tedy (Indonesian Society of Applied Science, 2024)
The Bogor District Government plans to use Bus Rapid Transit as one of the modes of mass transportation which is expected to increase the attractiveness of public transportation so as to reduce the use of private vehicles as an effort to reduce the level of traffic congestion. Determining the location and number of bus stops has an important role in the use of mass public transportation. The purpose of this study is to get the number and location of bus stops that can meet the potential demand, as well as the number of fleets needed for the operation of Mass Public Transport. The method used in this research is the Department of Land Transportation equation analysis. In this study, the determination of the location and number of bus stops along the mass transit route corridor 5 Bogor Regency was carried out by identifying the location that caused the greatest generation and met the criteria for the location of bus stops. The selected location is then carried out a screening analysis which aims to get the number and location of bus stops that can meet the potential demand and can analyze the potential demand from each stopping point. The results of this analysis conclude that there are 17 selected stop locations along the route with an average potential demand of 1983.80 trips/hrs, and the number of fleets required is 10 units of vehicles.